The 'over-researched community': An ethics analysis of stakeholder views at two South African HIV prevention research sites. (December 2017) - Koen, Jennifer; Wassenaar, Douglas; Mamotte, Nicole
Abstract: Health research in resource-limited, multi-cultural contexts raises complex ethical concerns. The term 'over-researched community' (ORC) has been raised as an ethical concern and potential barrier to community participation in research. However, the term lacks conceptual clarity and is absent from established ethics guidelines and academic literature. In light of the concern being raised in relation to research in low- and middle-income countries (LMICs), a critical and empirical exploration of the meaning of ORC was undertaken. Guided by Emanuel et al.'s (2004) eight principles for ethically sound research in LMICs, this study examines the relevance and meaning of the terms 'over-research' and 'over-researched community' through an analysis of key stakeholder perspectives at two South African research sites. Data were collected between August 2007 and October 2008. 'Over-research' was found to represent a conglomeration of ethical concerns often used as a proxy for standard research ethics concepts. 'Over-research' seemed fundamentally linked to disparate positions and perspectives between different stakeholders in the research interaction, arising from challenges in inter-stakeholder relationships. 'Over-research' might be interpreted to mean exploitation. However, exploitation itself could mean different things. Using the term may lead to obscured understanding of real or perceived ethical concerns, making it difficult to identify and address the underlying concerns. It is recommended that the term be carefully and critically interrogated for clarity when used in research ethics discourse. Because it represents other legitimate concerns, it should not be dismissed without careful exploration. Highlights: Examines key South African stakeholders perspectives of the term 'over-researched community' (ORC). Finds that the term 'over-research' mirrors a wide range of ethical concerns and existing tensions in research ethics. Argues that claims of 'over-research' should be cautiously and critically interrogated.